Effects of Cu2O thickness on the photoelectrochemical properties of Cu2O/WO3 heterostructure. (January 2023) - Fu, Yajun; Yang, Jingxin; Wang, Jin; Cao, Linhong
Abstract: Designing and controlling heterostructures are able to effectively improve the photoelectrochemical performance of WO3 . Here, we controlled the thickness of Cu2 O film to improve the photoelectrochemical performance of Cu2 O/WO3 heterostructures. The Cu2 O/WO3 heterostructures with different Cu2 O layer thicknesses (from 70 to 657 nm) were successfully prepared by reactive magnetron sputtering. The developed heterostructures improved the photoelectrochemical performance and showed good stability and reliability. The Cu2 O/WO3 heterostructure with 440 nm Cu2 O layer exhibited the highest photocatalytic degradation rate of 38% after 5 h for MB in this work, which was about 2.5 times higher than that of the pure WO3 film. To understand the phenomena, we analyzed the optical absorption, photoluminescence spectra, transient photocurrent response, and the Mott-Schottky curves of the Cu2 O/WO3 heterostructures, which revealed that the built-in electric field at the interface dominate the efficient separation of the photogenerated electron-hole pairs. Furthermore, the charge separation efficiency of the built-in electric field was tuned by the thickness of Cu2 O layer. Our results indicate that tuning the materials thickness is an efficient way to optimize the photoelectrochemical performance of composite films. Highlights: The Cu2 O/WO3 heterostructures exhibited Cu2 O layer thickness dependent photocatalytic performance. The charge separation efficiency of the Cu2 O/WO3 heterostructures was greatly tuned by the thickness of Cu2 O. A favorable thickness of Cu2 O in Cu2 O/WO3 is beneficial to take full advantage of the built-in electric field. The optimal Cu2 O layer thickness of Cu2 O/WO3 heterostructures in this work is about 440 nm.